Roman drama and its contexts - Frangoulidis, S; Harrison, S; Manuwald, G (De Gruyter, 2016)
This edited collection aims to address this issue: it includes 33 contributions by an international team of scholars, discussing single plays or Roman dramatic genres (including comedy, tragedy and praetexta, from both the Republican and ...